Soil Stabilization Using Waste Paper Fly Ash: Precautions for Its Correct Use - Hani Baloochi; Diego Aponte; Marilda Barra (Applied Sciences, 2020)
This paper deals with the valorization of waste paper fly ash (WPFA) as a binder for soil stabilization. The mineralogical characterization shows the presence of free lime, as well as some non-reactive and cementitious phases. The hydration of lime is an expansive reaction and can be problematic in soil stabilization. Therefore, to study its effect on stabilized soil, an in-house experimental set-up is proposed to measure the possible expansion. Furthermore, to study the effect of water reduction and delay time on strength, unconfined compressive strength with different mixes is conducted. The obtained results showed that using WPFA causes expansion in stabilized soil, but a delay time of 30 min, after mixing the material with water and then compacting it, can decrease the expansion. Additionally, decreasing the water content by a point of Proctor can be essential for improving the strength in soil samples, even reaching the same strength values as control samples cured at 7 days. Finally, all the results obtained in this study have shown that WPFA is a suitable material for use as a binder for soil stabilization while reducing its optimum water content, adding a proper delay time, and taking into consideration WPFA’s expansive behavior at the moment of its use.